Reconfigurable Yagi-Uda antenna based on a silicon reflector with a solid-state plasma. Issue 1 (December 2017) - Kim, Da-Jin; Park, Jang-Soon; Kim, Cheol; Hur, Jae; Kim, Choong-Ki; Cho, Young-Kyun; Ko, Jun-Bong; Park, Bonghyuk; Kim, Dongho; Choi, Yang-Kyu
Abstract This paper describes the fabrication and characterization of a reconfigurable Yagi-Uda antenna based on a silicon reflector with a solid-state plasma. The silicon reflector, composed of serially connected p-i-n diodes, forms a highly dense solid-state plasma by injecting electrons and holes into the intrinsic region. When this plasma silicon reflector is turned on, the front-realized gain of the antenna increases by more than 2 dBi beyond 5.3 GHz. To achieve the large gain increment, the structure of the antenna is carefully designed with the aid of semiconductor device simulation and antenna simulation. By using an aluminum nitride (AlN) substrate with high thermal conductivity, self-heating effects from the high forward current in the p-i-n diode are efficiently suppressed. By comparing the antenna simulation data and the measurement data, we estimated the conductivity of the plasma silicon reflector in the on-state to be between 104 and 105 S/m. With these figures, silicon material with its technology is an attractive tunable material for a reconfigurable antenna, which has attracted substantial interest from many areas, such as internet of things (IoT) applications, wireless network security, cognitive radio, and mobile and satellite communications as well as from multiple-input-multiple-output (MIMO) systems.